Prophylactic use of levosimendan in preoperative setting for surgical repair of congenital heart disease in children - Wannaz, L.; Boillat, L.; Perez, M. H.; Di Bernardo, S. (Frontiers in Pediatrics, 2023)
Introduction: Low cardiac output syndrome (LCOS) is a significant cause of morbidity and the leading cause of mortality after pediatric cardiac surgery. Levosimendan has been shown safe and effective in pediatrics to treat LCOS. We aimed to review our local strategy with preoperative prophylactic Levosimendan infusion to minimize LCOS after heart surgery in identified high-risk patients. Methods: Retrospective monocentric study. As there is no reliable cardiac output measurement in children, we recorded hemodynamic parameters as surrogates of cardiac output after extracorporeal circulation through an electronic patient survey system at different time points. Results: Seventy-two children received Levosimendan before surgery between 2010 and 2019. As expected, most patients were newborns and infants with prolonged open-heart surgeries. Median cardiopulmonary bypass time was 182 [137-234] min, and aortic clamping time was 95 min. The postoperative hemodynamic parameters, vasoactive-inotropic score, and urine output remained stable throughout the first 48 hours. Only a tiny portion of the patients had combined surrogate markers of LCOS with a maximal median arterial lactate of 2.6 [1.9-3.5] mmol/L during the first six postoperative hours, which then progressively normalized. The median arterio-venous difference in oxygen saturation was 31 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] % between 12-18 hours post-surgery and gradually decreased. The median venous-to-arterial CO2 difference was the highest at 10 [7-12] mmHg between 12-18 hours post-surgery. Nine patients (13%) required extracorporeal membrane oxygenation. No patient required dialysis or hemofiltration. Mortality was 0%. Conclusion: Before congenital heart surgery, preoperative prophylactic administration of Levosimendan seems effective and safe for decreasing occurrence and duration of LCOS in high-risk children.